2004
DOI: 10.1007/s10545-005-0457-3
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding experience in inborn errors of metabolism other than phenylketonuria

Abstract: Breastfeeding has been recommended for the dietary treatment of infants with phenylketonuria, but studies documenting clinical experience in other inborn errors of metabolism are very few. Seven infants diagnosed with methylmalonyl-CoA mutase deficiency (n=2), ornithine carbamoyltransferase deficiency (n=1), propionic acidaemia (n=1), isovaleric acidaemia (n=1), maple syrup urine disease (n=1) and glutaric acidemia type I (n=1) were tried with breastfeeding over two years. After the control of acute metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 1 publication
1
15
0
9
Order By: Relevance
“…[6][7][8][9][13][14][15] Even in the presence of certain risk factors for definitive weaning, which are inevitable in this situation, we consider that the breastfeeding duration of the children with PKU was very good and that it was comparable to the mean durations described in the literature, both for children with PKU and for Brazilian children without PKU. 13,16,17 Demirkol et al, 13 McCabe et al 10 and Motzfeldt et al 6 found mean breastfeeding duration in phenylketonuric patients of 6.1, 8.9 and 7.0 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][13][14][15] Even in the presence of certain risk factors for definitive weaning, which are inevitable in this situation, we consider that the breastfeeding duration of the children with PKU was very good and that it was comparable to the mean durations described in the literature, both for children with PKU and for Brazilian children without PKU. 13,16,17 Demirkol et al, 13 McCabe et al 10 and Motzfeldt et al 6 found mean breastfeeding duration in phenylketonuric patients of 6.1, 8.9 and 7.0 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…. Entretanto, para que a utilização do LM tenha êxito no tratamento da PKU, é necessário que os pacientes tenham consultas freqüentes no serviço de referência, possibilitando ajustes dietéticos constantes e controle metabólico adequado, evitando níveis indesejáveis de phe no sangue [6][7][8][9][13][14][15] . Mesmo na presença de alguns fatores de risco, inevitá-veis nesta situação, para o desmame definitivo, consideramos que a duração da amamentação das crianças com PKU foi muito boa e semelhante aos tempos médios descritos na literatura, tanto para crianças com PKU quanto para crianças brasileiras sem PKU 13,16,17 .…”
Section: Métodosunclassified
“…Despite this, breastfeeding is less common in individuals with PKU than in the general population (Agostoni et al 2000a). In view of the major biological and developmental advantages, and when feasible or not contraindicated, human breast milk and breastfeeding should be given greater consideration in PKU and other inborn errors of metabolism than is currently granted (Huner et al 2005;MacDonald et al 2006a). …”
Section: Human Breast Milk and Breastfeedingmentioning
confidence: 99%